A correspondence of modular forms and applications to values of L-series - Diamantis, Nikolaos; Neururer, Michael; Strömberg, Fredrik (SpringerOpen, 2015)
An interpretation of the Rogers–Zudilin approach to the Boyd conjectures is established. This is based on a correspondence of modular forms which is of independent interest. We use the reinterpretation for two applications to values of L-series and values of their derivatives.